Polymer processing : principles and modeling - Agassant, J.-F (Hanser Publishers ; Hanser Publications, 2017)
Engineering of polymers is not an easy exercise: with evolving technology, it often involves complex concepts and processes. This book provides the theoretical essentials: understanding of processes, a basis for the use of design software, and much more.